2022
DOI: 10.3390/biomedicines10082054
|View full text |Cite
|
Sign up to set email alerts
|

Production of Reactive Oxygen Species by Epicardial Adipocytes Is Associated with an Increase in Postprandial Glycemia, Postprandial Insulin, and a Decrease in Serum Adiponectin in Patients with Severe Coronary Atherosclerosis

Abstract: Purpose. This work investigates the relations between the production of reactive oxygen species (ROS) by epicardial adipose tissue (EAT) adipocytes and parameters of glucose/insulin metabolism, circulating adipokines levels, and severity of coronary atherosclerosis in patients with coronary artery disease (CAD); establishing significant determinants describing changes in ROS EAT in this category of patients. Material and methods. This study included 19 patients (14 men and 5 women, 53–72 y.o., 6 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…This paracrine organ, nestled between the visceral pericardium and the outer myocardial surface, exerts significant influence on both local and systemic inflammatory and atherogenic processes through adipokine production and secretion [1,6,[26][27][28]]. EAT's direct linkage to CVD is increasingly recognized as more impactful than general obesity [2,9,29,30]. The disruption of the balance between cardioprotective and deleterious effects contributes systemically to the development and progression of CAD.…”
Section: Study Implications and Literature Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This paracrine organ, nestled between the visceral pericardium and the outer myocardial surface, exerts significant influence on both local and systemic inflammatory and atherogenic processes through adipokine production and secretion [1,6,[26][27][28]]. EAT's direct linkage to CVD is increasingly recognized as more impactful than general obesity [2,9,29,30]. The disruption of the balance between cardioprotective and deleterious effects contributes systemically to the development and progression of CAD.…”
Section: Study Implications and Literature Analysismentioning
confidence: 99%
“…The disruption of the balance between cardioprotective and deleterious effects contributes systemically to the development and progression of CAD. Excessive adiposity in EAT has been shown to release inflammatory cytokines, augmenting endothelial dysfunction, increasing oxidative stress, and, consequently, accelerating coronary atherosclerosis [8,9,22]. A growing body of evidence suggests that excessive epicardial adiposity is an independent risk factor for CVD.…”
Section: Study Implications and Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperglycemia and insulin resistance accelerate adipocyte oxidative stress ( 57 59 ). A recent study showed that patients with severe coronary atherosclerosis, glucose and insulin metabolic disorder, and serum adiponectin reduction are significantly linked with higher oxidative stress in EAT adipocytes ( 60 ). In addition, EAT thickness was related with endothelial dysfunction ( 61 ), and it was concluded that EAT may predict the early reversible stages of atherosclerosis.…”
Section: Epicardial Adipose Tissue: a New Biomarker For Cardiovascula...mentioning
confidence: 99%